2021
DOI: 10.1093/cdn/nzab104
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Use of the Veggie Meter® for Spectroscopy-Based Skin Carotenoid Measurements in the Research Setting

Abstract: Carotenoids are a class of phytochemical compounds found in a variety of fruits and vegetables (F/V) and therefore, are commonly used as a biomarker for F/V intake. The Veggie Meter® is a non-invasive research-grade instrument that detects and quantifies carotenoids in the skin. To determine current practices and examine variability among users, a survey was administered to researchers using the device (n = 19, response rate = 35.8%) and variation in anatomical site preparation, calibration, number of measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 46 publications
(56 reference statements)
0
24
0
Order By: Relevance
“…The Veggie Meter ® is a validated, research-grade instrument that utilizes pressure-mediated reflection spectroscopy to estimate carotenoid concentration in the skin [ 11 ]. The protocol for collecting data using the Veggie Meter ® , including triplicate measures and the use of the non-dominant ring finger, was followed to ensure that inter- and intra-individual variability, as well as environmental interferences, were minimized [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Veggie Meter ® is a validated, research-grade instrument that utilizes pressure-mediated reflection spectroscopy to estimate carotenoid concentration in the skin [ 11 ]. The protocol for collecting data using the Veggie Meter ® , including triplicate measures and the use of the non-dominant ring finger, was followed to ensure that inter- and intra-individual variability, as well as environmental interferences, were minimized [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The current study also improves upon the data collection methods of the previous research. Earlier studies were limited to food frequency questionnaires and self-reported purchasing; the present study includes two 24-h dietary recalls to measure F&V intake, an imperfect gold standard for dietary data collection [ 25 ], and uses the Veggie Meter ® to assess dermal carotenoids, an objective measure that has been correlated with F&V intake [ 19 , 20 ]. We will also use a standardized point of sale (POS) software to capture purchasing across communities and mobile market programs.…”
Section: Discussionmentioning
confidence: 99%
“…Skin carotenoids will be assessed using the commercially available Veggie Meter ® (Longevity Link, Inc., Salt Lake City, UT, USA), which relies on reflection spectroscopy to measure the level of carotenoid pigments. Emerging evidence supports the use of spectroscopy-based skin carotenoid measurements as a noninvasive objective method for determining skin carotenoid concentrations indicative of F&V intake [ 19 , 20 ]. We will ask participants to clean their hands with an alcohol wipe before inserting the left index finger into the meter.…”
Section: Methodsmentioning
confidence: 99%
“…After the publication of more research using the Veggie Meter ® , the protocol evolved to include hand cleaning and the use of the non-dominant ring finger [42]. Since completion of this study, users of the Veggie Meter ® worked together to create a comprehensive set of recommendations for use in different research settings [53]. Future studies utilizing the Veggie Meter ® in this population should follow these guidelines to ensure consistency with other research.…”
Section: Discussionmentioning
confidence: 99%